THE RELATIVE ABUNDANCES AND PILE NEUTRON CAPTURE CROSS SECTIONS OF THE ISOTOPES OF SAMARIUM, GADOLINIUM, DYSPROSIUM AND YTTERBIUM - WALKER, WILLIAM HERBERT (My University, 1956)
A double-focusing mass spectrometer has been used to determine the relative abundances of the isotopes of naturally- occurring platinum, samarium, gadolinium, dysprosium and ytterbium. The relative abundances of a portion of the four rare earth elements were also measured after bombardment in a high neutron flux for a period of six months. From a comparison of the results for the irradiated and unirradiated samples the neutron absorption cross sections of the individual isotopes have been calculated.